Nocturnal indicators of increased cardiovascular risk in depressed adolescent girls. (6th November 2015) - Waloszek, Joanna M.; Woods, Michael J.; Byrne, Michelle L.; Nicholas, Christian L.; Bei, Bei; Murray, Greg; Raniti, Monika; Allen, Nicholas B.; Trinder, John
Summary: Depression is an independent risk factor for cardiovascular disease in adults, and recent literature suggests preclinical signs of cardiovascular risk are also present in depressed adolescents. No study has examined the effect of clinical depression on cardiovascular factors during sleep. This study examined the relationship between clinical depression and nocturnal indicators of cardiovascular risk in depressed adolescent girls from the general community (13–18 years old; 11 clinically depressed, eight healthy control). Continuous beat‐to‐beat finger arterial blood pressure and heart rate were monitored via Portapres and electrocardiogram, respectively. Cardiovascular data were averaged over each hour for the first 6 h of sleep, as well as in 2‐min epochs of stable sleep that were then averaged within sleep stages. Data were also averaged across 2‐min epochs of pre‐sleep wakefulness and the first 5 min of continuous non‐rapid eye movement sleep to investigate the blood pressure dipping response over the sleep‐onset period. Compared with controls, depressed adolescents displayed a similar but significantly elevated blood pressure profile across sleep. Depressed adolescents had significantly higher systolic and diastolic blood pressure and mean arterial pressures across the entire night ( P < 0.01), as well as during all sleep stages ( P < 0.001). Depressed adolescents also had higher blood pressure across the sleep‐onset period, but the groups did not differ in the rate of decline across the period. Higher blood pressure during sleep in depressed adolescent females suggests that depression has a significant association with cardiovascular functioning during sleep in adolescent females, which may increase risk for future cardiovascular pathology.